Dynamic expression of molecules that control limb muscle development including Fhl1 in hind limbs of different gestational age. Issue 9 (30th January 2014) - Li‐Li, Wang; Zhao‐Hong, Peng; Yang, Fan; Lian‐Yong, Li; Di, Wu; Yi, Zhang; Jia‐Ning, Miao; Yu‐Zuo, Bai; Zheng‐Wei, Yuan; Wei‐Lin, Wang; Kai‐Lai, Sun
<x xml:space="preserve">Abstract</x> Muscle abnormality could be a key reason for congenital clubfoot (CCF) deformity, which manifests itself during fetal development. FHL1 down‐regulated expression is involved in the formation of skeletal muscle abnormalities in CCF and FHL1 gene mutations contribute to the development of some kinds of myopathies. Therefore, detecting dynamic expression of Fhl1 and other molecules (Hgf, MyoD1, Myogenin, and Myh4) that control limb muscle development in hind limbs of different gestational age will provide a foundation for further research on the molecular mechanism involves in the myopathies or CCF. The dynamic gene expression levels of Fhl1, Hgf, MyoD1, Myogenin, and Myh4 in the lower limbs of E16, E17, E19, and E20 rat embryos were examined by real‐time RT‐PCR. Immunofluorescence was used to detect formation of specific muscle fibers (fast or slow fibers) in distal E17 hind limbs. The expression levels of Fhl1, Hgf, MyoD1, Myogenin, and Myh4 were varying in hind limbs of different gestational age. Real‐time PCR results showed that all the genes that control skeletal muscle development except for Fhl1 exhibited a peak in E17 lower limbs. Immunofluorescence results showed obviously positive fast‐myosin in the distal E17 lower limbs and meanwhile slow‐myosin had no apparently signals. E17 was a critical time point for terminal skeletal muscle differentiation in the lower limbs of rat embryos.